2018
DOI: 10.1029/2018gb005897
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Upper Tidal Estuary in Wetland Blue Carbon Storage and Flux

Abstract: Carbon (C) standing stocks, C mass balance, and soil C burial in tidal freshwater forested wetlands (TFFW) and TFFW transitioning to low‐salinity marshes along the upper estuary are not typically included in “blue carbon” accounting, but may represent a significant C sink. Results from two salinity transects along the tidal Waccamaw and Savannah rivers of the U.S. Atlantic Coast show that total C standing stocks were 322–1,264 Mg C/ha among all sites, generally shifting to greater soil storage as salinity incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 113 publications
0
105
0
1
Order By: Relevance
“…The Waccamaw middle forest site will continue to experience increased periods of salinity of 0.5–2 psu, thus facing the threat of potential reduction of plant growth and potential change in the composition of species in the community (Krauss, Duberstein, et al, ). However, stress on this site will not necessarily come from saltwater intrusion, rather from hydrology regime changes, as flooding could become the limiting factor on this site in the future (Conner et al, ; Cormier et al, ; Krauss et al, ; Thomas et al, ). For this forest site, flood frequency, duration, and timing may be more important than slight increases in porewater salinity on maintaining forest productivity (e.g., litterfall) and soil N dynamics (e.g., soil total N, foliar N, litter C/N ratio) during drought (Cormier et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Waccamaw middle forest site will continue to experience increased periods of salinity of 0.5–2 psu, thus facing the threat of potential reduction of plant growth and potential change in the composition of species in the community (Krauss, Duberstein, et al, ). However, stress on this site will not necessarily come from saltwater intrusion, rather from hydrology regime changes, as flooding could become the limiting factor on this site in the future (Conner et al, ; Cormier et al, ; Krauss et al, ; Thomas et al, ). For this forest site, flood frequency, duration, and timing may be more important than slight increases in porewater salinity on maintaining forest productivity (e.g., litterfall) and soil N dynamics (e.g., soil total N, foliar N, litter C/N ratio) during drought (Cormier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our modeling simulation showed that under a nondrought year, mean porewater salinity would be 2.1 ± 1.4 psu at the Waccamaw site and 3.6 ± 2.4 psu at the Savannah site. Mean annual soil porewater salinities during 2005–2016 were 3.1 ± 0.5 psu at the Waccamaw marsh site and 4.9 ± 0.5 psu at the Savannah marsh site, respectively (Krauss et al, ). These data indicate that the two marsh sites will be unable to maintain their current oligohaline marsh (<2–5 psu) species composition and associated productivity and soil biogeochemical processes in the future with climate change and SLR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations